The Problem of the GDR’s Foreign Policy Identity in the Context of Initiatives in Africa in the 1960s - 1980s - Natalia V. Ivkina (Vestnik RUDN. International Relations)
The article is devoted to an examination of the German Democratic Republic’s (GDR) foreign policy identity in the context of its policy in Sub-Saharan Africa. The relevance of this topic is primarily determined by the fact that the African vector of the GDR’s foreign policy course still influences the current state of the German state’s agenda in the region under study. The objective of this study is to identify the characteristics of the GDR’s foreign policy course in Sub-Saharan Africa in the context of three dimensions: narrative, performative and emotional. As a theoretical basis, it is proposed to test two alternative points of view, the realist/neorealist and the liberal. These theories imbue the notion of foreign policy identity with diverse meanings, offering researchers the opportunity to test them on historical and relevant cases. Critical theory, which is also included in the theoretical discourse of this work, has tried to go a little further by considering the role of alliance formation for the state identity. The scientific novelty lies in by the fact that most studies on the identity of East Germany describe the sociological aspect, while the specifics of foreign policy initiatives remain outside the brackets. The following research methods were chosen historical and chronological, which allowed not only to study the dynamics of relations between the GDR and individual African countries, but also to assess the level of cooperation between them. In several cases, the comparative method was relevant for breeding the independent policy of the GDR and joint initiatives with the Soviet Union, as well as for comparing East German and West German initiatives. Finally, a content analysis of mutual visits between the GDR and African countries helped to find that the increase in the number of visits was due to the expansion of the areas of interaction between the sides - from primarily economic cooperation to security policy coordination. The author draws conclusions confirming certain theoretical postulates stated in the theoretical and methodological basis of the study and provides an assessment of all three dimensions of the GDR’s foreign policy identity.